2011
DOI: 10.1016/j.neuropharm.2010.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Functional reduction of SK3-mediated currents precedes AMPA-receptor-mediated excitotoxicity in dopaminergic neurons

Abstract: In primary cultures of mesencephalon small-conductance calcium-activated potassium channels (SK) are expressed in dopaminergic neurons. We characterized SK-mediated currents (ISK) in this system and evaluated their role on homeostasis against excitotoxicity. ISK amplitude was reduced by the glutamatergic agonist AMPA through a reduction in SK channel number in the membrane. Blockade of ISK for 12 h with apamin or NS8593 reduced the number of dopaminergic neurons in a concentration-dependent manner. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 84 publications
3
33
1
Order By: Relevance
“…If NS13001 indeed acted in our experiments by reducing “metabolic burden” on SCA2 PC cells, it is likely that NS13001 and related compounds may offer potential benefit not only for cerebellar ataxias but also for PD and for other neurodegenerative disorders that affect SK2 or SK3-expressing pacemaking neurons. This hypothesis is consistent with recently reported neuroprotective effects of CyPPA in experiments with dopaminergic neuronal cultures (Benitez et al, 2011; Herrik et al, 2012). The data in the current manuscript suggest that NS13001 should exert even more potent protective effect than CyPPA on SNc neurons both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…If NS13001 indeed acted in our experiments by reducing “metabolic burden” on SCA2 PC cells, it is likely that NS13001 and related compounds may offer potential benefit not only for cerebellar ataxias but also for PD and for other neurodegenerative disorders that affect SK2 or SK3-expressing pacemaking neurons. This hypothesis is consistent with recently reported neuroprotective effects of CyPPA in experiments with dopaminergic neuronal cultures (Benitez et al, 2011; Herrik et al, 2012). The data in the current manuscript suggest that NS13001 should exert even more potent protective effect than CyPPA on SNc neurons both in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 93%
“…From these results we conclude that NS13001 holds promise as a potential therapeutic agent for treatment of SCA2 and possibly other cerebellar ataxias. We reasoned that NS13001 may also be useful for treatment of other neurodegenerative disorders that affect pacemaking cells expressing SK2/3 channels, such as for example dopaminergic neurons in SNc (Benitez et al, 2011; Chan et al, 2009, 2010; Surmeier, 2007; Surmeier et al, 2010). Evaluation of NS13001 in animal models of ataxia, PD and other neurodegenerative disorders will be required to test these predictions.…”
Section: Significancementioning
confidence: 99%
“…The availability of mice with the kit mutation that lack ICC-IM allowed investigators to explore the role of ICCs in neurotransmission. Early studies reported complete loss of neurotransmission in these mutant mice (3,4,6), suggesting that ICC-IM indeed play a pivotal role in neurotransmission. However, more recent studies have called this conclusion into question (1,10,16,31,37).…”
Section: Discussionmentioning
confidence: 91%
“…Intracellular Ca 2ϩ changes were obtained by sequential illumination at 340 and 380 nm and expressed as the fluorescence ratio (F R). Both Ca 2ϩ rise and decay times were analyzed as previously described (4,17). Global Ca 2ϩ rise time was measured as the time needed for the rise from 10 to 90% of maximum, fitted with exponential growth.…”
Section: Camentioning
confidence: 99%
“…(Benítez et al, 2011) showed that the non-selective 1-EBIO as well as CyPPA, two chemically very disparate molecules, were able to counteract AMPA neurotoxicity on DA neurons in culture. The protective role of SK channels was further strengthened by showing that both the peptide blocker apamin and the small molecule negative modulator NS8593 accelerated the death of DA neurons.…”
Section: Discussionmentioning
confidence: 99%